Hyperbaric oxygen therapy in alleviating cerebral ischemia-reperfusion injury via the BMP6/Smad-hepcidin pathway - Lan-Zhao Wang; Ji-Hong Zhang; Ji-Min Shi; Xiu-Ju Li (PLoS ONE, 2026)
Cerebral ischemia-reperfusion injury (CCI) is a cause of neurological damage. Hyperbaric oxygen therapy (HBOT) can improve recovery in CCI in relation to iron metabolism and ferroptosis, but the precise mechanisms remain unclear. This study aims to explore the neuroprotective effects of HBOT in CCI and its regulator of iron homeostasis via BMP6/Smad-Hepcidin signaling pathway. Male Wistar rats were divided into Control (CT), Ischemia-Reperfusion (GM), Ischemia-Reperfusion + Normobaric Hyperoxia (NH), and Ischemia-Reperfusion + HBOT (HO) groups. The CCI model was induced by four-vessel occlusion. HBOT was administered at 2.5 ATA for 120 minutes daily for 5 days. Neurological function was assessed using the modified neurological severity score, light-dark box, and Morris Water Maze test. Histopathological analysis, transmission electron microscopy, Nissl and TUNEL staining, oxidative stress markers, Western blotting and qPCR were used to assess neuronal damage, mitochondrial integrity, necrosis, apoptosis, oxidative stress, iron metabolism and BMP6/Smad-Hepcidin mRNA expression and protein concentrations. HBOT significantly improved neurological function, reduced neuronal damage, and preserved mitochondrial integrity compared to untreated animals. Oxidative stress markers, including malondialdehyde and antioxidant enzyme activities were significantly restored. HBOT also downregulated the BMP6/Smad-Hepcidin pathway, leading to decreased hepcidin levels. Western blot and qPCR analysis confirmed the suppression of ferroptosis-related markers in the HBOT group. HBOT significantly reduces neurological deficits, neuronal damage, and oxidative stress in CCI injury. Its neuroprotective effects are likely mediated by the regulation of the BMP6/Smad-Hepcidin pathway and the suppression of ferroptosis. These findings suggest that HBOT is a promising therapeutic strategy for treating CCI.